Sustainable Mobility and Traffic Safety at the Local Level - Lep, Marjan; Moharić, Matej (11. Nacionalna konferenca o varnosti v lokalnih skupnostih: Odpornost lokalnih skupnosti na varnostna tveganja, 2025)
The paper discusses traffic safety as an integral element of sustainable mobility in the urban environment, with a special emphasis on the impact of personal motor traffic speed and on the (subjective) feeling of safety of residents. Based on surveys, traffic data and spatial analyses collected in the process of the Municipal Integrated Transport Strategy of the City of Maribor, the paper shows the gap between professionally set goals and perceptions of space users. Although numerous technical and infrastructural improvements have been implemented, residents often do not assess the environment as safe enough, which inhibits the modal shift to walking, cycling and public transport. The paper concludes by emphasising public acceptance of measures, consistent monitoring of indicators and long-term behavioural changes as key conditions for a lasting improvement in traffic safety in cities.